Evaluating Profitability and Its Impact on Productivity in Commercial Banks (An Applied Research in a Sample of Iraqi Private Banks) - Ahmad Ali Hussain; Ibrahim Fadul Al Moula (Journal of Madenat Alelem University College, 2021)
The research problem is to determine the nature of the relationship between profitability and banking productivity in the shadow of the assessment of profitability, it is necessary in shadow of the multiplicity of commercial banks with the presence of government banks, to assess the financial performance of banks to find out the strengths and weaknesses and identify them in order to survive and continue in the competition market and achieve the highest profits in shadow of intense competition between these banks. The research aims to clarify the concept of profitability and banking productivity and the metrics used in its evaluation, In addition to measuring and analyzing the banking profitability and productivity according to its own standards, and find out how important it is in the sustainability of banks, In addition to looking for the relationship between profitability ratios and banking productivity. Therefore the research starts from stems from the main hypothesis that "the use of profitability indicators and banking productivity scale Malmquist enables banks to evaluate their financial performance accurately and enable them to improve their profitability and productivity". The results of the research showed that Gulf Commercial Bank and United Bank for Investment recorded the highest profitability ratios, In addition that seventeen banks achieved an increase in total productivity according to the variable returns volume model, The banks that achieved a decline in total productivity during the research period amounted to eighteen banks, which means that most banks need to improve the level of productive performance through the exploitation of resources and possibilities available.